Collection and Conservation of Genetic Resources of Tropical Root and Tuber Crops for Sustainable Livelihood . A Status Report - Dwivedi, N.K.; Asha, K.I.; Asokan Nair, R.; Indiradevi, A.; Suma, A. (JOURNAL OF ROOT CROPS, 2014)
Roots and tuber crops are important subsidiary or subsistence food and nutritional crops in tropical and sub tropical countries. India is a unique place for the production of diverse horticultural crops. Genetic diversity is needed to develop improved varieties through different breeding programmes. Collection and conservation of genetic resources of tropical roots and tuber crops in India is carried out by National Bureau of Plant Genetic Resources (NBPGR), New Delhi with its regional stations located in different agro-ecological regions and Central Tuber Crops Research Institute (CTCRI), Thiruvananthapuram, Kerala with its regional station at Bhubaneswar. The regional station of NBPGR at Thrissur is primarily meant to undertake plant genetic resources activities in the tropical humid region of the country. This station has since 1977 collected considerable genetic variability in these crops and their wild relatives from the southern region. A sizable number of collections of cassava, sweet potato, yams, aroids, Chinese potato, arrowroot and wild relatives of Amorphophallus and Dioscorea, made from different parts of Andhra Pradesh, Goa, Karnataka, Kerala, Tamil Nadu, Union Territories of Lakshadweep and Andaman and Nicobar Islands are being maintained in the Field Gene Bank (FGB). The germplasm of these crops were characterized and evaluated for different useful characters. Four accessions in four different species of Dioscorea (IC 202328, 202370, 202382 and 202383) were registered for diosgenin content, a unique trait. Twelve accessions belonging to Dioscorea are also being maintained under in vitro cultures at this station. A total of 1075 accessions comprising of elephant foot yam (50), Amorphophallus spp. (6 spp., 30), Chinese potato (31), taro (415), lesser yam (64), greater yam (166), Dioscorea spp. (11 spp., 133), cassava (156) and cassava in vitro cultures (30) were transferred to CTCRI, Thiruvananthapuram. CTCRI has been identified as the National Active Germplasm Site (NAGS) for FGB maintenance and further proper utilization of these crops. In future, unexplored tribal areas of the region would be surveyed for new germplasm collections. The available germplasm of these crops and their wild relatives would be further exploited and used to develop new varieties with desirable superior traits through different crop improvement programmes for the sustainable livelihood of the farmers, tribal people and local population in this fast changing agro-climate scenario.